Island Ecological Tourism: Constructing Indicators of the Tourist Service System in the Penghu National Scenic Area - Hsiao, Chih Yu; Kuo, Chun Min; Tuan, Chao Lin (Frontiers in Ecology and Evolution, 2021)
It is critical to developing a sustainable ecotourism service system for the fragile Penghu National Scenic Area in Taiwan. This study, therefore, adopted the fuzzy Delphi method and analytic hierarchy process (AHP) to establish an index framework. The results identified four dimensions with 21 service factors. The findings are as follows. Safety management capability is found to be the main factor in the ecotourism service system. Ecological diversity is essential for the marine environment and the core resource for ecotourism; the transportation capacity and environmental quality need to be improved. Marine environmental resources are indispensable to the development of ecotourism. In addition, the local community must support ecotourism, natural resources should be protected, and the development of ecotourism needs to support the sustainability of local conservation. Therefore, encouraging local residents and stakeholders to attend and promote ecotourism, establishing a safety management system for ecotourism, developing environmental protection regulations for tourists in ecotourism, and improving tourist satisfaction. The government needs to develop guidelines for the protection of marine resources, plan an ecotourism service system, and improve public and transportation infrastructure to make it safe and accessible.